Radiative model for the microquasar SS433: Non-thermal emission from the eastern jet - Sotomayor Checa, Pablo Omar (2021)
In this work we propose a lepto-hadronic model for the non-thermal emission of the eastern jet of the galactic microquasar SS433. We obtain that the flux in TeV reported by the HAWK Collaboration can be explained by the decay of neutral pions produced in inelastic collisions proton-proton. Radio and X-ray emission is correctly fitted by synchrotron radiation of relativistic primary electrons.